Evaluation of new biomarkers in stage III and IV endometriosis - Evrim Ebru Kovalak; Tolga Karacan; Oğuzhan Zengi; Özlem Karabay Akgül; Şefik Eser Özyürek; Hakan Güraslan (Taylor & Francis Group, 2023)
Objective To investigate the efficacy of new endometriosis biomarkers in diagnosis and treatment.Methods Thirty women with Stage III-IV endometriosis who were given an indication for surgery and 49 control patients were compared. Preoperative and postoperative serum levels of Annexin A5 (ANXA5), soluble intercellular adhesion molecule-1 (sICAM-1), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), soluble vascular cell adhesion molecule-1 (sVCAM-1), vascular endothelial growth factors (VEGF) and Ca-125 measurements were compared.Results AUCs of ANXA5, sICAM-1, IL-6, TNF-α, VCAM-1, VEGF biomarkers were not found to be significant in diagnosing endometriosis when evaluated alone (p > 0.05). Only the AUC of the Ca-125 biomarker values were found to be significant with 73% sensitivity and 98% specificity (p < 0.001). However, when Ca-125 and ANXA5 were evaluated together, it was concluded that the diagnosis of endometriosis could be made with 73% sensitivity and 100% specificity.Conclusion When Ca-125 and ANXA5 are evaluated together, it seems to be more valuable than Ca-125 alone in diagnosing endometriosis.